Evaluasi Kenyamanan Termal di Lingkungan Tropis: Studi Parametrik Morfologi Perkotaan Hipotetis di Jakarta - Gede Krishna Bhakta; Nedyomukti Imam Syafii (Universitas Muhammadiyah Palembang, 2024)
The significant growth of cities worldwide led to more than half of the global population residing in urban areas, with urbanization projected to have reached 68% by 2050. However, this growth also brought negative impacts on urban environments, one of which was the Urban Heat Island (UHI) effect, where urban areas with dense buildings experienced higher temperatures than their suburban counterparts. Urban morphology, which focused on the formation and transformation of urban areas, served as a crucial indicator for urban planning, information management, and urban climate applications. The increased urban air temperatures significantly influenced the outdoor thermal comfort (OTC) of urban residents. This study aimed to establish a relationship between urban morphology and outdoor thermal comfort in tropical climates using the Universal Thermal Climate Index (UTCI) to assess thermal comfort. The research findings indicate that larger Building Site Coverage leads to lower UTCI values, suggesting improved thermal comfort. Conversely, smaller building site coverage results in higher UTCI values, indicating less favorable thermal comfort. Simulation analysis of Outdoor Thermal Comfort reveals a distribution of cooler thermal conditions between buildings on the east and west sides, while the north and south sides experience warmer thermal conditions.